CRISPR-Cas based precision genome editing: current advances and associated challenges in crop improvement and trait enhancement - Samanwaya Niraula; Rasik Khanal; Nischal Ghimire (Genetics & Applications)
The CRISPR-Cas system has revolutionized precision genome editing and opened up enormous prospects for crop improvement and trait enhancement. This review covers recent advances related to the application of CRISPR-Cas in agricultural biotechnology, with an emphasis on its potential to contribute to solving critical issues of food security and sustainability. Global population is expected to reach 10 billion by 2050, presenting a challenge that demands new approaches to raise agricultural productivity. The review investigates the mechanisms by which CRISPR-Cas systems, especially Cas9 and Cas12a, facilitate precise alterations in plant genomes, leading to augmented resilience against both biological and environmental challenges. Significant accomplishments comprise increased drought resistance, enhanced disease tolerance, and improved nutritional quality in agricultural species such as wheat, maize, and soybean. However, the application of CRISPR-Cas technology encounters challenges, including regulatory hurdles and public acceptance. This paper underlines modern achievements together with future possibilities, at the same time paying much attention to the connected challenges and emphasizing the crucial role of CRISPR-Cas technology for the advancement of sustainable agriculture. Using such a powerful tool, scientists aim at creating resistant crop species that will be able to meet the needs of the growing population while providing food safety and quality.